The Model of Impulse Buying: Consider Price Discounts and Store Displays - Nunung Ayu Sofiati; Lili Suryati; Wikrama Wardana; Nana Trisnawati; April Gunawan Malau; Andriasan Sudarso; Albert Gamot Malau (Journal of Accounting and Finance Management, 2023)
This research endeavors to investigate the effects of Impulse Buying Discount Price and In-Store Display on Borma Departement Store Bandung. Additionally, it seeks to determine the combined influence of Price Discount and In-Store Display on Borma Departement Store Impulse Buying in Bandung. The study employs a descriptive quantitative methodology and involves the analysis of data collected from 980 customers at Borma Departement Store Terrain, with 91 respondents selected using a formula method. Both library and field research are used to gather data systematically and objectively. The analytical method used is descriptive analysis, and the findings indicate that Price Discount has a significant positive effect on Impulse Buying, while In-Store Display has a partially positive and significant impact on this phenomenon. The combination of discounted pricing and eye-catching in-store displays can effectively stimulate impulse purchases.